2021
DOI: 10.1021/acs.inorgchem.1c01232
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Complementary Components Using a Tripodal Bismuth Compound: Pnictogen Bonding or Coordination Chemistry?

Abstract: Triple pnictogen bonding refers to the ability of a pnictogen atom to engage in three simultaneous pnictogen bonds (PnBs) to a complementary partner through a single pnictogen atom. This supramolecular strategy was recently introduced as a unique facet of pnictogen bonding as compared to other named supramolecular interactions. Here, the ability of bismuth to participate in this phenomenon is demonstrated using Bi((NC 9 H 7 ) 3 CH 3 ). The study reveals that Bi engages in stronger PnBs than the analogous Sb sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 53 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…Sb and Bi are used as an efficient pnicogen bonding donors for formation of supramolecular architectures in solution, solid state, catalysis, etc. [75][76][77]. In this context, the propensity of nitrogen, being the third most electronegative element with its extremely low polarizability, to act as a pnicogen bond donor remains questionable.…”
Section: Carbon Bonding Pnicogen Bonding and Hydrophobic Interactionsmentioning
confidence: 99%
“…Sb and Bi are used as an efficient pnicogen bonding donors for formation of supramolecular architectures in solution, solid state, catalysis, etc. [75][76][77]. In this context, the propensity of nitrogen, being the third most electronegative element with its extremely low polarizability, to act as a pnicogen bond donor remains questionable.…”
Section: Carbon Bonding Pnicogen Bonding and Hydrophobic Interactionsmentioning
confidence: 99%
“…It is commonly held that the three σ-holes generated around a PnX 3 molecule would be conducive to the formation of up to three PnBs [ 97 , 98 ]. For example, the Cozzolino group [ 99 ] identified three such bonds in the internal geometry of Bi((NC 9 H 7 ) 3 CH 3 ) that persist in solution. A detailed examination of this question [ 100 ] provided a nuanced answer in the general case.…”
Section: Discussionmentioning
confidence: 99%
“…According to the molecular electrostatic potential mapping of BiAz, as drawn in Figure S17, it was shown that BiAz could have a positive potential on hypervalent bismuth. 19 The area of the positive potential in BiAz is more expansive than that in TAz (Figure S17). These results imply that the effective Lewis acidity of hypervalent bismuth might be stronger than that of hypervalent tin.…”
Section: Nmr Spectroscopic Analysismentioning
confidence: 99%